Simple library cataloging - Akers, Susan Grey (American Library Association, 1954)
This book has a three-fold purpose: (1) to give to the librarian of the small public, school, college, or special library who lacks professional education and experience under expert guidance the necessary directions for classifying cataloging a collection of printed and audio-visual material, that they may be made accessible; (2) to serve as a textbook for short elementary courses in cataloging; and (3) to serve as collateral reading in the earlier part of the basic cataloging sourses